Characterization Of Polyhydroxybutyrate Properties As Additives Blend Material In Additive Manufacturing For Biomedical Device Fabrication - Muhammad Zulhilmi Bin Zainuddin (Universiti Sains Islam Malaysia, 2025)
Matric: 3201280 (FKP)